Development of Self-Regulation in Adolescents in the Context of Educational Process - Popova S.I (Moscow State University of Psychology and Education, 2018)
The paper reviews the issue of self-regulation development in adolescents as the process of supporting favourable and transforming unfavourable emotional states appropriate to the performed joint activity. Experiencing intense emotions makes personal growth more difficult for the adolescent, and therefore the task of promoting self-regulation becomes extremely important. Our hypothesis was that the development of self-regulation contributes to the adolescent's ability to recognize and interpret emotional states and extends the range of practices available to him/ her. Creating operative images of an object in concrete situations has a mediated effect on the transformation of the emotional states experienced by the adolescent. The revealed social psychological conditions were implemented through role-based forms of group activities, methods and means of self-regulation development. We evaluate the effectiveness of the development of self-regulation in adolescents based on certain criteria and analyse the outcomes of an experimental study. The ideas proposed in this paper can be used in the formation of regulative universal learning actions in adolescents at school to develop their ability to consciously regulate emotional states in the context of implementing the federal state education standards.